Peran Penyuluh Agama Dalam Menekan Angka Perceraian Di Wilayah KUA Kecamatan Pekalongan Utara Tahun 2017-2019 - Chayati, Nur (Al-Hukkam: Journal of Islamic Family Law, 2021)
The divorce rate in the North Pekalongan District KUA Region from 2017 to 2019 has experienced ups and downs. The increase in the number of divorce cases in 2017 was 41 cases from 2016 which was only 32 cases, while divorce in 2017 decreased by 4 cases from the previous year 2016 there were 11 cases of divorce. In 2018 there were 4 cases of divorce and 26 cases of divorce. However, in 2019 there was a significant spike for divorce, rising to 16 cases and for divorce, there were 58 cases. The type of research carried out by this researcher is Field Research, namely research that is directly related to the object under study by object observation and interviews. The data analysis technique that will be used by researchers in this study is "qualitative analysis" which is a research method that uses and produces data in a descriptive analysis. The results of this study indicate that the reality of the divorce rate in the KUA Region of North Pekalongan District in 2017-2019 has experienced ups and downs. Then in 2018 the role of religious instructors was very good, this was shown by the decline in the divorce rate at that time, and in 2019 the divorce rate experienced a large spike, however, the role of religious instructors was still there, but could not suppress the divorce rate.